Access to Energy Revealing through Socio-economic Status Survey of the Local People for Rural Electrification in Nawalparasi - Dhakal, Bhola Nath (Economic Review of Nepal, 2019)
Rural electrification program seems to be crucial to improve living conditions and promote development. The main objective of this study was to identify the socio-economic status of the local people and also measure their perception on willingness to pay for hydroelectricity in two rural municipalities of Nawalparasi East district. The study has followed both qualitative and quantitative methods for socio-economic survey. Household questionnaire survey, Focus Group Discussion and Key Informant Interview techniques have been applied for primary data collection. In addition, secondary data has been compiled through published and unpublished documents from field as well as central level. Agriculture and livestock rising have been found the major sources of income in this area. Therefore, the non-farm source of income is very low. However, remittance from foreign job playing vital role as another source of income for the livelihood of the people. As being economically capable and socially aware with modern facilities and its implication on better and easier life support in future, the local peoples from the study area has been found encouraging. Whole area of the study site has not available electricity facility and their positive willingness to pay for hydroelectricity is the major finding and step forward for the future planning of regular and reliable power supply to uplift their socio-economic condition, reduce poverty and support on rural development activities.